Structural, spectroscopic (FT-IR, NMR, UV-visible), nonlinear optical (NLO), cytotoxic and molecular docking studies of 4-nitro-isonitrosoacetophenone (ninapH) by DFT method - Küçük, İlhan; Kaya, Yunus; Kaya, A. Asli (Elsevier, 2017)
(4-Nitro-phenyl)-oxo-acetaldehyde oxime (ninapH) is a type of oxime, which has a oxime and alpha-carbonyl groups. This molecule has been synthesized from literature procedure. The structural properties and conformational behaviors were examined using the density functional theory (DFT) with the B3LYP method combined with the 6-311++G(d,p) basis set. As a result of the conformational studies, the most stable conformer was determined, and then this molecule was optimized with the same basis set. Comprehensive theoretical and experimental structural studies on the molecule have been carried out by FT-IR, NMR and UV-vis spectrometry. The calculated HOMO and LUMO energies show that charge transfer within the molecule. The first order hyperpolarizability and molecular electrostatic potential (MEP) were also performed. The thermodynamic properties (heat capacity, entropy, and enthalpy) of the ninapH have been calculated at different temperatures, 100-1000 K. In addition, the molecular docking studies have been, performed with DNA and protein structures (downloaded from Protein Data Bank). (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Carbonyloxime; DFT; Spectroscopy; Band gap; Nonlinear optics; Molecular docking